Cardiovascular Autonomic Neuropathy and Glucose Variability in Patients With Type 1 Diabetes: Is There an Association? - Nyiraty, Szabolcs; Pesei, Fruzsina; Orosz, Andrea; Coluzzi, Sara; Vági, Orsolya Eszter; Lengyel, Csaba; Ábrahám, György; Frontoni, Simona; Kempler, Peter; Várkonyi, Tamás (Frontiers in Endocrinology, 2018)
A relationship is suspected between autonomic neuropathy (AN) and glucose variability (GV) as variability is associated with oxidative stress responsible for neuronal damage while the impaired autonomic function has a detrimental effect on metabolism. The oxidative stress associated with glucose variability might be responsible for neuronal damage while autonomic neuropathy has a detrimental effect on metabolism. The aim of the study was to find relationship between AN and GV in type 1 diabetic patients and to identify further factors that affect GV. The aim of the study was to find relationship between AN and GV in type 1 diabetic patients and to determine further factors in the pathogenesis of GV. Patients and methods: 20 type 1 diabetic patients were involved (age: 39.5±3.4 years, duration of diabetes: 17.5±2.5 years; HbA1c: 8.1±0.2%, mean±SE). AN was assessed by the cardiovascular reflex tests (CRT). The interstitial glucose levels were determined following insertion of a subcutaneous electrode during the continuous glucose monitoring (CGM) method on 6 consecutive days. GV was characterized by calculation of 4 parameters. Results: Standard deviation of interstitial glucose values (SD) correlated positively with the overall AN score and the degree of the orthostatic reduction of systolic blood pressure (AN-score-SD ρ=0.47, p<0.05; orthostasis- SD: ρ=0.51, p<0.05). Mean Absolute Glucose: (MAG) correlated with 3 parameters of AN (AN-score-MAG: ρ=0.62, p<0.01; 30/15 ratio-MAG: ρ= -0.50, p<0.05; orthostasis- MAG: ρ=0.59, p<0.01). The HbA1c also correlated with 2 parameters of GV (HbA1c – Continuous Overlapping Net Glycaemic Action [CONGA]: ρ=0.56, p<0.05; HbA1c- MAG: ρ=0.45, p<0.05). The frequency of hypoglycemia did not exhibit any correlation with measures of GV. Conclusions: Severity of glycemic variability but not overall glucose load correlates with both parasympathetic and sympathetic dysfunctions in long-standing type 1 diabetes. Higher HbA1c is associated with more severe glucose variability. The observed correlation between increased glucose variability and the severity of AN necessitates the further exploration of this relationship.